Developing a Requirements Model for Software Projects - Gheni, Ali Yahya; Muhasin, Haifaa Jassim Muhasin; Yousif, Hiba Adil; Yusmdi Yah Jusoh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Requirements elicitation is recognized as one of the most critical activities in the software development process as it has an impact on its success. Studies such as the CHAOS Report, a study based on The [Standish Group]'s CHAOS Research Project on IT project success rates and project management best practices report, indicate that about half of the factors associated with project success are related to requirements. Previous studies showed several problems related to requirements elicitation. This paper tried to find out the existing requirements models for software projects and how to develop a new requirements model for software projects. The requirements system was developed by Visual Studio 2019. Online model verification was conducted with 6 experts from the IT industry. After the system was developed, it was validated by three developers/programmers from the same industry (functional test/white-box testing) and eleven developers (non-functional test/black-box testing). The results of the model verification supported the model of requirements. Additionally, the requirements system was validated by non-functional test/black-box testing and functional test/white-box testing